2013
DOI: 10.1371/journal.pone.0067726
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Spatio-Environmental Drivers of Human Settlement: An Eigenvector Based Variation Decomposition

Abstract: The relative importance of deterministic and stochastic processes driving patterns of human settlement remains controversial. A main reason for this is that disentangling the drivers of distributions and geographic clustering at different spatial scales is not straightforward and powerful analytical toolboxes able to deal with this type of data are largely deficient. Here we use a multivariate statistical framework originally developed in community ecology, to infer the relative importance of spatial and envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although human modification indices do not convey the entire human effect expressed as changes historically accumulated over natural ecosystems, they are useful to infer the spatial pattern and extent of the capacity of humans to transform the earth through land use [ 11 ]. Many studies analyze how diverse ecological regions have different capacity to respond to landscape transformations (e.g., [ 12 , 13 ]), but only a few of them (e.g., [ 14 – 16 ]) analyze how the physical geography (defined, for example, as biomes or ecoregions) affects the spatial patterns of human modification.…”
Section: Introductionmentioning
confidence: 99%
“…Although human modification indices do not convey the entire human effect expressed as changes historically accumulated over natural ecosystems, they are useful to infer the spatial pattern and extent of the capacity of humans to transform the earth through land use [ 11 ]. Many studies analyze how diverse ecological regions have different capacity to respond to landscape transformations (e.g., [ 12 , 13 ]), but only a few of them (e.g., [ 14 – 16 ]) analyze how the physical geography (defined, for example, as biomes or ecoregions) affects the spatial patterns of human modification.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous work has found that reduced species richness is associated with increased nitrogen deposition (Payne et al, 2017) -another environmental variable associated with human development (though the effect of nitrogen on species richness is inconsistent; Peñuelas et al, 2013;Pescott & Jitlal, 2020;Sasaki et al, 2010;Seastedt & Vaccaro, 2001). Indeed, where humans settle on a landscape is non-random (Antrop, 2004;Pickett & Cadenasso, 1995;Vandam et al, 2013) and these confounding variables may influence diversity. Additional work is hence needed to disentangle the relative importance of different variables associated with human development.…”
Section: Ecological Patterns Human Development and Nonnative Speciesmentioning
confidence: 99%
“…For example, the spatial effects of social dilemmas have been investigated for several decades ( Nowak and May, 1992 ; Hauert, 2006 ) and the frequency of human cooperation and collaboration or selfishness and exploitation across spatial dimensions impacts the resilience of groups of peoples and their ability to maintain high productivity ( Alvard, 2004 ; Jimenez et al, 2008 ). Furthermore, spatial patterns of human settlements and population densities may be related to community stability in the face of perturbation events such as loss of water, tillable soil, hunting ground, food, energy and other resources, as well as the related incidents of overpopulation and politico-military conflicts ( Tir and Diehl, 1998 ; Vandam et al, 2013 ). In this context, densities of refugee settlements across countries and subsequent patterns of repopulation of cities after wars may reveal human community and ethno-regional group stability properties in the face of significant devastation.…”
Section: Pasmore In the Broader Context Of Spatial Resilience Measurementioning
confidence: 99%